GDF-15 and hepcidin as a therapeutic target for anemia in chronic kidney disease - Naglaa Makram Farag; Mahmoud Mousa; Eman Elsayed; Ahlam Ismeil (BMC, 2023)
Abstract Background Anaemia is a common presenting feature among patients with chronic kidney disease (CKD) and associated with poor clinical outcomes. We evaluated the diagnostic validity of growth differentiation factor-15 (GDF-15) and hepcidin as it is not clear if they are useful as a biomarkers of anaemia among non-dialysis CKD egyptian patients. Method An analytical cross-sectional study was conducted among non-dialysis CKD patients (n = 60) and apparently healthy controls (n = 28) at Minia University maternity & children Hospital. Serum levels of GDF-15 and hepcidin were determined. Predictive logistic regression models were built and post estimation receiver operator characteristics were determined to evaluate diagnostic validity of hepcidin and GDF-15 for iron deficiency anaemia. Results Hepcidin and GDF-15 are significantly higher in cases than control p value (0.047 < 0.0001) respectively. The predictive value of diagnosing anaemia among CKD patients using hepcidin and GDF-15 was 72.0%, 70.0%. There was a weak negative correlation between hepcidin levels and glomerular filtration rate GFR (r = -.175, p = 0.105) in CKD patients, and significant correlation between serum GDF-15 and haemoglobin (r = -0.897, p < 0.0001), ferritin (r = 0.489, P < 0.000), Iron (r = -0.314, P = 0.002), CRP (r = 0.409, P < 0.0001). Conclusion Hepcidin and GDF-15 is a potential biomarker for predicting anaemia connected with inflammation among CKD Egyptian patients.